LRRC6 regulates biogenesis of motile cilia by aiding FOXJ1 translocation into the nucleus - Dong Yun Kim; Yu Jin Sub; Hye-Youn Kim; Kyeong Jee Cho; Won Il Choi; Yo Jun Choi; Min Goo Lee; Friedhelm Hildebrandt; Heon Yung Gee (Cell Communication and Signaling, 2023)
Abstract Background LRRC6 is an assembly factor for dynein arms in the cytoplasm of motile ciliated cells, and when mutated, dynein arm components remained in the cytoplasm. Here, we demonstrate the role of LRRC6 in the active nuclear translocation of FOXJ1, a master regulator for cilia-associated gene transcription. Methods We generated Lrrc6 knockout (KO) mice, and we investigated the role of LRRC6 on ciliopathy development by using proteomic, transcriptomic, and immunofluorescence analysis. Experiments on mouse basal cell organoids confirmed the biological relevance of our findings. Results The absence of LRRC6 in multi-ciliated cells hinders the assembly of ODA and IDA components of cilia; in this study, we showed that the overall expression of proteins related to cilia decreased as well. Expression of cilia-related transcripts, specifically ODA and IDA components, dynein axonemal assembly factors, radial spokes, and central apparatus was lower in Lrrc6 KO mice than in wild-type mice. We demonstrated that FOXJ1 was present in the cytoplasm and translocated into the nucleus when LRRC6 was expressed and that this process was blocked by INI-43, an importin α inhibitor. Conclusions Taken together, these results hinted at the LRRC6 transcriptional regulation of cilia-related genes via the nuclear translocation of FOXJ1. Video Abstract